1976
DOI: 10.1021/jf60208a002
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral confirmation and analysis by the Hall detector of mirex and photomirex in Herring Gulls from Lake Ontario

Abstract: decane (photomirex), were discovered in the whole body lipid of Herring Gulls from Pigeon Island, Lake Ontario. PCBs, which were evident in high concentrations, coeluted with Mirex and photomirex in residue cleanup procedures, and interfered with their determination by electron-capture gas chromatography (EC-GC) using standard analytical columns. Samples were perchlorinated to remove this interference, and structures were confirmed by gas chromatography /mass spectrometry (GC/MS). The Hall electrolytic conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
3
10
0
Order By: Relevance
“…58,59 The 8-monohydromirex compound was previously named photomirex because photolysis was the most probable route for its formation in Lake Ontario. 60 Mudambi and Hassett (1988) 61 subsequently showed that 8-monohydromirex was formed in Lake Ontario water by photolysis of a chargetransfer complex with dissolved organic matter. Formation of 8-monohydromirex competes with loss, which accounts for the longer half-time (8.5 y) of this compound compared to other CHCs in Lake Ontario (Table 5).…”
Section: Mirex-related Compoundsmentioning
confidence: 99%
“…58,59 The 8-monohydromirex compound was previously named photomirex because photolysis was the most probable route for its formation in Lake Ontario. 60 Mudambi and Hassett (1988) 61 subsequently showed that 8-monohydromirex was formed in Lake Ontario water by photolysis of a chargetransfer complex with dissolved organic matter. Formation of 8-monohydromirex competes with loss, which accounts for the longer half-time (8.5 y) of this compound compared to other CHCs in Lake Ontario (Table 5).…”
Section: Mirex-related Compoundsmentioning
confidence: 99%
“…Mirex accumulates primarily in adipose tissue, liver, kidneys, and brain [3]. Mirex and its major degradation product (photomirex) have been isolated in soil samples, fish, birds, and mammals throughout the United States [4][5][6][7][8]. Because of its environmental stability and lipophilic properties, mirex is considered a potential hazard to human and animal health.…”
Section: Introductionmentioning
confidence: 99%
“…The surprising discovery of mirex in Lake Ontario fish (1) sparked a considerable effort to monitor mirex concentrations in sediment (2) and various species of fish (3) from the lake. In the course of investigating the levels of mirex in herring gulls, which were proposed as a monitor species for organochlorine contamination of the Great Lakes, photomirex (8monohydromirex) was discovered to be an important environmental contaminant as well as mirex (4,5). Levels of photomirex were estimated to be greater than 30% of mirex levels in eggs over the period [1972][1973][1974][1975].…”
mentioning
confidence: 99%